MENGUKUR KONSEPTUALITAS PENGUJIAN PERATURAN PEMERINTAH PENGGANTI UNDANG-UNDANG MEASURING CONCEPTUALITY OF JUDICIAL REVIEW OF GOVERNMENT REGULATION IN LIEUW OF LAW - Zamroni, Mohammad (Jurnal Legislasi Indonesia, 2011)
In circumstances which forced the crisis, according to the constitution the presidentis given the right to establish government regulations in the legislation replacement (oftenabbreviated Perppu). at the same time, based upon Constitution of the Republic ofIndonesia Year 1945 and the law 10 of 2004 on Legislation Procedure, perpu thesame position or in parallel with the law. Therefore, the issuance and executionperppu closely monitored by the parliament through the mechanism of approval orrejection as defined in the constitution. However, in practice not uncommon in thedeviation or deviation to the implementation of constitutional mechanisms such perppu.of them is about the execution time inconsistency or delivery to the House for approvalor perpu perpu rejection. in addition, concerning the legal status at the time wasrejected by Parliament perppu perppu formal justice also cause problems. based on these things, it must be the Judicial Review Perppu the constitutional court for thesake of the constitution and rule of law in Indonesia.